Development of the PjBL-SSI-Based Soundwise E-Module for Fifth-Grade Elementary Science Learning on Sound and Its Properties - Mega Sukima Ardiyanti; Erna Suhartini; Rosita Putri Rahmi Haerani; Hesti Samsulistia Sari (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to develop and validate an e-module based on Project-Based Learning (PjBL) and Socio-Scientific Issues (SSI) for fifth-grade elementary science learning on sound and its properties, and to assess its validity through expert assessments of the material, media, and language aspects. Methodology: This study employed a Research and Development (R&D) approach, using a modified 4D model comprising the Define, Design, and Development stages. The e-module was created with digital design tools and incorporated Project-Based Learning (PjBL) and Socio-Scientific Issues (SSI) approaches. Data collection involved expert validation sheets and questionnaires, which were analyzed using descriptive quantitative methods and percentage calculations. Main Findings: The validation results demonstrated that the developed e-module received high validity scores from experts: 97% from material experts, 92% from media experts, and 95% from language experts. These findings suggest that the e-module is highly valid, suitable, and feasible as a learning resource in elementary science education, especially for the topic of sound and its properties. Novelty/Originality of this study: The novelty of this study lies in the integration of Project-Based Learning and Socio-Scientific Issues within a single interactive e-module design for elementary science learning. This integration provides contextual, inquiry-based learning experiences that connect abstract scientific concepts with real-world issues, thereby enhancing conceptual understanding and supporting meaningful learning in elementary education.